Utilizing Canva to Foster Innovation in Early Childhood Education Learning Materials - Imroatus Sholihah; Imron Arifin; Sa'dun Akbar (Jurnal Pendidikan Islam, 2026)
Digital technological advancements require early childhood educators to develop more innovative learning media that align with the characteristics of digital-native children. To meet this need, the use of modern design platforms has become increasingly important. This study aims to explore the use of the graphic design platform Canva in fostering innovation in early childhood education (ECE) instructional materials. Focusing on the digital native generation of children, the study evaluates the effectiveness of Canva in assisting educators in designing creative, interactive, and developmentally appropriate learning media. A qualitative research method was employed. Data were collected through observations, in-depth interviews with ECE educators, and analysis of Canva-based instructional design outputs. The findings indicate that Canva enhances educators’ creativity in developing visually appealing and pedagogically relevant learning materials. Canva’s intuitive features-such as interactive templates, child-friendly illustrations, and easy design sharing-have proven to facilitate the creation of enjoyable and memorable learning experiences for young children. The implications of this study suggest that the use of graphic design technology like Canva can serve as an effective strategy for developing innovative ECE instructional content. The study recommends systematic training for educators to maximize Canvas potential as a technology-based learning support tool.